2010
DOI: 10.1177/1534735410383171
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Functional Analyses Reveal the Potential Involvement of Endoplasmic Reticulum Stress and α-CP1 in the Anticancer Activities of Oridonin in HepG2 Cells

Abstract: Oridonin has been shown to exhibit therapeutic effects against hepatocellular carcinoma (HCC) in vitro and in vivo. This study aimed to identify the anti-HCC mechanisms of oridonin in HepG2 cells using proteomic and functional analyses. MTT assay showed that oridonin treatment for 24 hours dose-dependently inhibited cell growth with an IC 50 value of 40.4 mM. Treatment with 40 mM oridonin for 24 hours induced apoptosis determined by nuclear morphologic changes of DAPI-stained cells and flow cytometric analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Rabdosia rubescens is an effective traditional Chinese medicine for the treatment of hepatoma. 9 As its main component, oridonin has been proven to inhibit the progression of HCC. The potential mechanism may be associated with the regulation of mitochondrial ROS and ES stress to induce cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rabdosia rubescens is an effective traditional Chinese medicine for the treatment of hepatoma. 9 As its main component, oridonin has been proven to inhibit the progression of HCC. The potential mechanism may be associated with the regulation of mitochondrial ROS and ES stress to induce cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanism may be associated with the regulation of mitochondrial ROS and ES stress to induce cell apoptosis. For example, it has been reported that oridonin activates oxidative stress pathways leading to HepG2 cell death, Hsp70-1 is a key protective protein in oridonin-mediated oxidative stress, 14 oridonin modulates ER stress and α-CP1, leading to proliferation inhibition and apoptosis induction in HCC cells, 9 and oridonin-induced HCC cell apoptosis is mediated by mitochondrial ROS through PARP activation, p53, and the MAPK pathway. 15 , 16 In addition, considering that oridonin could effectively inhibit HCC, many researchers have extracted oridonin derivatives, which have also been proven to have significant inhibitory effects on the progression of HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HepG2 cells, multiple mechanisms, including the inhibition of telomerase, induction of endoplasmic reticulum stress and regulation of p53, MAPK and mitochondrial signaling pathways, have been implicated in the apoptotic activity of oridonin ( 25 , 49 , 50 ). Whether other mechanisms, such as PARP activation, are associated with the anti-HepG2 activity of oridonin remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Among the pharmacological activities mentioned above, the anticancer effect of oridonin has drawn increasing attention in recent years. Over the past decades, oridonin and its analogs have been demonstrated to exhibit potent anticancer activities by promoting apoptosis, 49 inducing cell cycle arrest, 50 inhibiting angiogenesis, 51 and suppressing metastasis 52 in a variety of cancer types, such as lung carcinoma, 53 hepatocellular carcinoma, 54 gastric cancer, 55 colorectal cancer, 56 breast cancer, 57 pancreatic cancer, 58 prostatic cancer, 59 and leukemia 60 . Furthermore, oridonin can induce autophagy, which contributes to apoptosis induction and inhibition of cancer progression in several cancer cell types, such as breast cancer cells 57 and colorectal cancer cells 56 .…”
Section: The Anticancer Activities Of Oridonin and Its Derivative Com...mentioning
confidence: 99%